Study Regarding the Teacher Training Related to Digital Technology in Romanian Educational System - Tita, Dumitrel-Victor; Bold, Nicolae; Popescu, Doru Anastasiu; Oprea, Mirela Georgiana; Trusca, Claudia Ionela (Didactica Danubiensis, 2025)
Technology plays an essential role in modernizing education, facilitating access to information, diversifying teaching methods, and increasing student involvement in the learning process. This study investigates teacher training in digital technology, analyzing the level of training, current skills and challenges encountered in the process of integrating technology into the educational process. The analysis was made on the Romanian educational system actors on a period extending on the first part of 2025. The study was developed in order to assess the level of skills and competencies of teachers related to the usage of digital technology in their role as a teacher and it is based on current competencies frameworks used at a national, European and global level, such as DigCompEdu. Some associations related to group profile and other professional indicators are made using statistical and unsupervised learning for specific results, such as classification. By extrapolation, the results can lead to the definition of several perspectives related to the design of training related to digital technology and its various usages.